Harshness, professionalism, dynamism, ﬂexibility or under the sign of the anniversary (Confluenţe Bibliologice, 2012)
Municipal Library „B.  P.  Hasdeu” has reached 135 years.  The Program „Days of Municipal Library „B.  P. Hasdeu” was held under the motto of innovation for the future: Rethinking, Redesigning, Revitalization, Reinvention, Regaining, various forms of cultural events insert with titles and impressive themes: colloquia, conferences, lessons, guests day, debates, book releases and journals, talk-show Library 3. 0, exhibitions of photos, journals, bibliographic information, totals of contests: videos Municipal Library „B.  P. Haşdeu” - 3. 0 Library, the Blog of the Year in the library network, communications- posters, projects-posters.